Comparison of sleep quality, shoulder function, and quality of life in patients with different-sized rotator cuff tears - Vergili, Ozge; Oktas, Birhan; Canbeyli, Ibrahim Deniz Deniz; Arikan, Halime; Aktas Arslan, Fatma Cansu (Asian Journal of Medical Sciences, 2021)
Background: Many patients with rotator cuff tears suffer from nocturnal shoulder pain resulting in sleep disturbance, inability on shoulder function, and reduced quality of life. Aims and Objective: This study aimed to compare patients with different sizes of rotator cuff tears (RCTs) concerning sleep quality, shoulder function, quality of life, and emotional state. Materials and Methods: Forty-four patients (mean age 49.43±10.71) with different size of RCT were included in this prospective cross-sectional study. Patients were divided into two groups according to RCT size diagnosed with magnetic resonance imaging. Patients were evaluated with Pittsburgh Sleep Quality Index (PSQI), Constant Murley (CM) score, Western Ontario Rotator Cuff Index (WORC), and Beck Depression Inventory (BDI). Results: There was no significant difference between patients with small and large size RCT in terms of sleep quality, shoulder functionality, quality of life and emotional state (p=0.841, p=0.258, p=0.916, p=0.936, respectively). Conclusion: We demonstrated that patients with RCT had poor sleep quality, decreased shoulder function, poor quality of life, and normal emotional status, regardless of the tear size.